Clinical Application and Efficacy Evaluation of Ginseng Extract Injections in the Repair of Skeletal Muscle Injuries in Athletes - Liu, Linjun; Kanti Das, Sreemoy; Jin, Zhuzhen (Journal of Theory and Practice in Engineering and Technology, 2024)
This study aimed to assess the clinical efficacy of Ginseng extract injections in promoting the recovery of skeletal muscle injuries among athletes. Methods: Forty athletes diagnosed with skeletal muscle injuries were treated with Ginseng extract injections across three specialized sports medicine clinics between May 2023 and January 2024. Each patient received weekly local injections for four consecutive weeks. Follow-up assessments were conducted over 12 to 48 weeks, with a mean follow-up duration of 20 weeks. Treatment efficacy was evaluated by measuring pain reduction, functional recovery, and recurrence rates. Results: Significant clinical improvement was observed in 35 out of 40 patients, yielding an overall efficacy rate of 87.5%. Three patients experienced a recurrence of their injuries within three months, and two patients showed no substantial improvement following treatment. Conclusion:Ginseng extract injections demonstrated considerable effectiveness in promoting skeletal muscle recovery with a low recurrence rate, indicating its potential for broader clinical application in managing sports-related muscle injuries.